Human Capital from Childhood Exposure to Homeownership: Evidence from Right-to-Buy - Richard Disney; John Gathergood; Stephen Machin; Matteo Sandi (CESifo GmbH, 2024)
"Right to Buy" (RTB) was a large-scale UK housing policy whereby incumbent tenants in public housing could buy their properties at heavily subsidised prices. The policy increased the national homeownership rate by over 10 percentage points between 1980 and the late 1990s. A key feature of RTB is that housing tenure changes did not involve residential mobility, as the policy bestowed homeownership on households in disadvantaged neighbourhoods in the public housing where they were already resident. This paper shows that exposure to RTB at birth significantly improved pupil performance in high-stakes exams and the likelihood to obtain a degree, while also improving labour earnings in young adulthood. The key drivers of these human capital gains are the wealth gains arising from the subsidy and the crime reduction generated by RTB. This is evidence of a novel means by which homeownership, and the resulting societal change and neighbourhood gentrification that accompanies it, contribute to increase human capital accumulation and improve educational and work outcomes for individuals in disadvantaged, low-income childhood settings.
Keywords: I21; I28; K14; R31; 330; human capital; homeownership; public housing